2010
DOI: 10.1177/000348941011900407
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Removal of Esophageal Impacted Dentures

Abstract: The dilation method using saline solution-soaked cotton slivers is relatively safe and effective in removing impacted dentures from the esophagus, avoiding open surgery and possible perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Fang 9 et al reported from 2008 through 2009, six patients with esophageal impacted denture were treated in their department on an emergency basis. There were four men (66.7%) and two women (33.3%) ranging in age from 40 to 76 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fang 9 et al reported from 2008 through 2009, six patients with esophageal impacted denture were treated in their department on an emergency basis. There were four men (66.7%) and two women (33.3%) ranging in age from 40 to 76 years.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologic examination, Fang et.al reveals that location of the dentures was in the upper esophagus in three cases and in the thorax in two cases; in one case it was in the lower esophagus. 9 Dentures are frequently made of acrylic resin, which is radiolucent, but the radioopaque wire clasps of the denture can some time be seen. 9 If a radiolucent foreign body is suspected, swallowing studies with contrast medium should be performed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Ingestion or self-insertion of foreign bodies by patients with psychiatric illnesses has also been reported. 3 A search of PubMed revealed only 2 cases of impaction of a wristwatch in the esophagus, 4,5 the other case was reported in India. 6 However, these foreign bodies were successfully removed by rigid endoscopy because there were no serious associated complications such as esophageal perforation.…”
Section: Discussionmentioning
confidence: 99%